Pengaruh Konten Pemasaran Digital Dan Kepercayaan Merek Terhadap Minat Berkunjung (Studi Pada Akun Instagram @jktbucketlist) - Audreansyah, Raeyaldi Novem; Meliana, Vina (UNIVERSITAS KALBIS, 2025)
The purpose of this study is to see the effect of digital marketing content and brand trust on visiting interest (study on @jktbucketlist Instagram account). This research uses a quantitative approach. Data was collected through distributing questionnaires with a Likert scale of 1-5 as a measurement of each statement. The number of samples applied was 115 respondents through the non-probability sampling method. The sample criteria are those who follow the @jktbucketlist Instagram account and have followed the @jktbucketlist Instagram account for more than 6 months. The results explain that digital marketing content affects visiting interest, brand trust affects visiting interest, and also simultaneously digital marketing content and brand trust affect visiting interest.